IMPLEMENTASI METODE BINET SIMON DAN METODE FUZZY LOGIC PADA APLIKASI TES KEMAMPUAN IQ (INTELLIGENCE QUOTIENT) DAN TIPE KECERDASAN (MULTIPLE INTELLIGENCE) UNTUK ANAK TUNARUNGU BERBASIS ANDROID - Andriat, Rio (TI S1 FKOM UNIKU, 2017)
AbstractThe first intelligence known by man is intelligence or intellectual acumen. Intelligence is mind intelligence, the intelligence function of thought can be used to solve a problem or situation quickly and precisely. Until now, many parents think that intelligence relates to calculations or any form of subjects that are difficult and challenging. However, in fact people have many forms of intelligence called intelligence type or multiple intelligences. This intelligence can be detected through psychological examination with measuring tools given in the form of the problems created by the psychologists to distinguish the person's behavior with others, improving self understanding, self evaluation, and self-acceptance. Intelligence is defined by IQ (Intelligence Quotient) which is grouped based on a comparison between the level of mental abilities (mental age) with age (chronological age). Based on test results, the android based application of IQ and multiple intelligence using Binet Simon method and Fuzzy Logic method for deaf children at SLB C YPALB Perwari Ancaran Kuningan can be done quickly, accurately, and the child's attention so that tests of IQ and multiple intelligence can be done more effective so that it can improve cognitive abilities and emotional, as well as the ability of intelligence of students, especially children with hearing impairment.Keywords Â : IQ test, multiple intelligence, deaf children, binet simon method, fuzzy logic method, based android.